"Изменным обычаем": Ливонская война и представления о государственной измене в России - Ерусалимский, К. (Соціум. Альманах соціальної історії, 2006)
The problem of betrayal is studied in the context of foreign office formation in Russia. It is also related to various socio-cultural categories associated with the so called chronographic history, political theology, imperial ideals and military ethics. The author demonstrates that during the Livonian War treason was interpreted as the main cause of Russia's failures on the international arena. Betrayal was considered to be «the motif», while the «crime» itself could vary from case to case. Fighting traitors the Muscovite lords fought ill thinking which the author had divided into several categories.